The gall of subordination: changes in gall bladder function associated with social stress. - Earley, Ryan L. (2004)
Diverse physiological and behavioural mechanisms allow animals to effectively deal with stressors, but chronic activation of the stress axis can have severe consequences. We explored the effects of chronic social stress on agonistic behaviour and gall bladder function, a critical but widely neglected component of stress-induced gastrointestinal dysfunction. Prolonged cohabitation with dominant individuals elicited behavioural modifications and dramatically increased bile retention in subordinate convict cichlid fish (Archocentrus nigrofasciatum). The key predictor of gall bladder hypertrophy was social subordination rather than status-related differences in food intake or body size. Stress-induced inhibition of gall bladder emptying could affect energy assimilation such that subordinate animals would not be able to effectively convert energy-rich food into mass gain. These results parallel changes in gall bladder function preceding cholesterol gallstone formation in humans and other mammals. Thus, social stress may be an important diagnostic criterion in understanding pathologies associated with gall bladder dysfunction.